Turkish history thesis and its aftermath. A story of modus operandi - (:unkn) unknown (My University, 2001)
The first part of this article introduces the reformulation of historical information and method to suit the requirements of the new political order in Turkey during the founding years of the Republic (1930s). This operation, initiated by Mustafa Kemal (Atatürk), started with history textbooks aimed at forming a standardised nation-state identity in the new generations. The intellectual origins, the premises, the aims, some specific features and the eventual, absolute victory of the "Turkish history thesis" (1936) is briefly summarised with reference to the new textbooks, the two history congreses (in 1932 and 1936) and the debates that highlighted historiographical problems. Ethnicity, i.e., Turkishness, pre-historical and early historical accounts of ethnic orgins, positivism in archaeological and linguistic research were the stress points of the thesis. The young nationalists of the era assumed the role of historians, while the criticisms, especially relating to methodological problems, raised by experienced historians were disregarded. The history thesis created a myth without method. The second part of the article traces the enduring problem of method through the later stages of Republican historiography. With reference to textbooks and other historiographical material from the 1970s, 1980s and 1990s, special attention is paid to the treatment of the history of the Turks, Ottoman history, and Republican history, as problematic issues of identity formation. Similar temporal, spatial and operational problems in narration are common to all these and other different subjects. The paper finally indicates the lack of debate on methodological problems of history teaching and history writing and excessive debate on degrees and variants of nationalism in present-day Turkish historiographical trends.
Keywords: 20th century; Historiography; Nationalism; Textbooks; Turkey